Horizontal movements of geomass in continental riftogenic geostructures (on the example of the Dnieper-Donets paleorift). Part 3. Systemic organization of post-rift reid deformations - Бартащук, Олексій Вацлавович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
Formulation of the problem. The article covers the results of tectonophysical studies on the structural manifestations of the collisional evolutionary stage of the continental crust, which complicate the riftogenic architecture of Dnieper-Donets paleorift. At the stages of platform activation, rocks in riftogenic structures acquire volumetric tectonic mobility due to internal structural-material transformations and deformation under the influence of reid tectonics. The structural manifestation of reid tectonics in the geological structure of the basement and sedimentary complexes of the Dnieper-Donetsk paleorift cover is the horizontal movement of its primary riftogenic segment tectonic elements, lineaments, geoblocks, tectonic structures and secondary deformation structure formation.Review of previous publications and studies. The paleotectonic situation in the paleorift before the start of the rifting is covered by the results of plate-tectonic reconstructions carried out for Ukrainian Shield. Structural-kinematic evolution of the continental crust in the adjacent territories of the Shield in the south was reproduced, covering the stages of collision with subduction of the crust and spreading followed by the extension of continental microplates. On this basis, the important role of ancient even-petty folded structures of sub-meridional extension is determined in the structure of paleorift foundation.Methods. In geotectonic studies an original technique was used for reconstructing the fields of tectonic deformations and tectonophysical analysis of geostructures, based on potential geophysical fields anomalies and vertical amplitudes of neotectonic movements.Results. It was established that structural waves of secondary deformations of horizontal-plane tectonic flow were formed under the influence of mechanisms of reid tectonics. It is shown that they determine the longitudinal tectonic segmentation of the modern paleorift structure. The tectonic position and natural kinematic mechanisms in the formation of the tectonic flow local structures, linear concentration zones of reid deformation of subregional and zonal scales, ranging in size from hundreds of meters to tens of kilometers, were studied.Scientific novelty and practical significance. In the regular submeridional direction of compression axis regional field of tectonic stresses, longitudinal structural waves of the volumetric tectonic flow of geomass formed in the sedimentary cover of the paleorift under the influence of the processes of reid tectonics. The natural mechanisms of reid deformation are caused by horizontal-planar displacements of structural elements, rocky ensembles of discontinuities and local structures of reid deformation dynamically conjugated with them. A common tectonic process of reid dynamic tectonics is collision warping of the sedimentary sequence horizons, which determines the main features of the system organization of the latest paleorift architecture and its modern longitudinal tectonic segmentation.